(untitled) (Revista horizonte, 2017)
Introduction: In free weight training there are many methodologies to train, test to do such exercises or to know what weights to lift, but scarcely how to extrapolate weights from a primary exercise to secondary exercises. The objective of this study was to develop a prediction equation, using the Maximum Repetition (MR) of the Flat Bench Press (PBP) as a mechanism to determine the maximum weights of five other exercises in active young people. Method: A non-experimental transectional design with descriptive-correlational scope was carried out with a sample of 15 university students 23.4Â±2.23 years old, who have a degree of experience in exercises with free weights; this work was carried out in order to predict the maximum weights to lift in 5 upper limb exercises (chest pull-up, French press, biceps curl, forearm curl and military press) from one exercise, Flat Bench Press (PBP). The statistical analysis was developed through a descriptive study integrating statistics of central tendency and variance, then the inferential study began with the Shapiro-Wilk normality test which determined the use of a Pearson correlation test (r) to estimate the level of association and a simple linear regression to evaluate the level of prediction in the equations. Results: A correlation was found between the PBP exercise and the derived exercises, being reflected in 5 different equations, one for each exercise. Conclusion: A proposal was obtained to extrapolate loads from the PBP considering five upper limb strength exercises. This proposal facilitates in precision, time and practice the calculation of strength based on a PBP exercise that acts as a predictor for other secondary strength exercises.